The basis of clinical tribalism, hierarchy and stereotyping: a laboratory-controlled teamwork experiment. Issue 7 (29th July 2016) - Braithwaite, Jeffrey; Clay-Williams, Robyn; Vecellio, Elia; Marks, Danielle; Hooper, Tamara; Westbrook, Mary; Westbrook, Johanna; Blakely, Brette; Ludlow, Kristiana
Abstract : Objectives: To examine the basis of multidisciplinary teamwork. In real-world healthcare settings, clinicians often cluster in profession-based tribal silos, form hierarchies and exhibit stereotypical behaviours. It is not clear whether these social structures are more a product of inherent characteristics of the individuals or groups comprising the professions, or attributable to a greater extent to workplace factors. Setting: Controlled laboratory environment with well-appointed, quiet rooms and video and audio equipment. Participants: Clinical professionals (n=133) divided into 35 groups of doctors, nurses and allied health professions, or mixed professions. Interventions: Participants engaged in one of three team tasks, and their performance was video-recorded and assessed. Primary and secondary measures: Primary: teamwork performance. Secondary, pre-experimental: a bank of personality questionnaires designed to assess participants' individual differences. Postexperimental: the 16-item Mayo High Performance Teamwork Scale (MHPTS) to measure teamwork skills; this was self-assessed by participants and also by external raters. In addition, external, arm's length blinded observations of the videotapes were conducted. Results: At baseline, there were few significant differences between the professions in collective orientation, most of the personality factors, Machiavellianism and conservatism. Teams generally functioned well, with effective relationships, and exhibited little by way of discernible tribal or hierarchical behaviours, and no obvious differences between groups (F (3, 31)=0.94, p=0.43). Conclusions: Once clinicians are taken out of the workplace and put in controlled settings, tribalism, hierarchical and stereotype behaviours largely dissolve. It is unwise therefore to attribute these factors to fundamental sociological or psychological differences between individuals in the professions, or aggregated group differences. Workplace cultures are more likely to be influential in shaping such behaviours. The results underscore the importance of culture and context in improvement activities. Future initiatives should factor in culture and context as well as individuals' or professions' characteristics as the basis for inducing more lateral teamwork or better interprofessional collaboration.